Initial Study of Invasive Approach of Electrical Capacitance Tomography for Identifying Non-Conducting Medium in Steel Pipe Application - Mohd Shahrul Md Jusob; Yasmin Abdul Wahab; Leow Pei Ling; Ruzairi Abdul Rahim; Suzanna Ridzuan Aw; Nurhafizah Abu Talip@Yusof; Rohana Abdul Karim; Nor Farizan Zakaria; Nurul Wahidah Arshad; Mohd Mawardi Saari; Zainah Md Zain; Mohd Anwar Zawawi; et al. (Penerbit UTM Press, 2024)
Indexed by MyCite